2022
DOI: 10.3389/fpubh.2022.873498
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Safety Climate and Hazards in the Industrial Sector: Gender Differences Perspective, Saudi Arabia

Abstract: BackgroundOccupational Health and Safety (OHS) has become a growing public health concern worldwide. A considerable body of literature has been generated around the theme of safety climate perceptions and occupational hazards, as many researchers have examined perceptions of the occupational safety climate in relation to organizational hierarchy. But there is an urgent need to address safety problems associated with gender differences, especially in Saudi Arabia, where women have only recently begun to work in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
1
1
Order By: Relevance
“…Consistent with previous research, our study showed that managers tended to perceive safety culture more positively than craft employees ( 9 – 11 ). Our research, however, was not able to fully support the seemingly consistent, yet limited research related to gender differences in safety culture perceptions ( 14 – 17 ). In our sample, male and female railroaders tended to have similar overall safety culture perceptions; that is, until we took management status into account.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Consistent with previous research, our study showed that managers tended to perceive safety culture more positively than craft employees ( 9 – 11 ). Our research, however, was not able to fully support the seemingly consistent, yet limited research related to gender differences in safety culture perceptions ( 14 – 17 ). In our sample, male and female railroaders tended to have similar overall safety culture perceptions; that is, until we took management status into account.…”
Section: Discussioncontrasting
confidence: 78%
“…Finally, work has examined how gender affects specific safety culture dimensions ( 14 ). In a sample of workers from five Saudi Arabian factories, gender differences were revealed on dimensions related to commitment to safety, prioritizing safety and caution, such that women tended to have higher scores than men.…”
Section: Safety Culture Perceptions Can Varymentioning
confidence: 99%
See 2 more Smart Citations
“…Aumentar a amostra e diversificá-la a nível nacional, uma vez que a recolha desta amostra seguiu uma metodologia de bola de neve, restringido-se mais à zona do Algarve, seria interessante para observar possíveis diferenças regionais e culturais, já que a ansiedade face à morte e o clima de segurança estão relacionados com fatores culturas (Arooj et al, 2022;Cicirelli, 2002). A maioria dos resultados obtidos pertencem ao género feminino, seria pertinente obter uma amostra mais homogénea, uma vez que estudos anteriores mostraram um traço de ansiedade mais alto para o género feminino (e.g., Fitri et al, 2020;Martínez-López et al, 2021) diferença esta também verificada para o clima de segurança e aceitação de risco (AlMousa et al, 2022).…”
Section: Limitaçõesunclassified